IBD 3 Weight-based prescribing of thiopurines may not accurately optimise metabolite levels in the safe and therapeutic range: a paediatric IBD study. (12th September 2022) - Barakat, Farah M; Lewis, Sophie; Ashton, James; Gilbert, Luke; Driscoll, Kouros; Barnes, Claire; Sholeye-Bolaji, Adebola; Phan, Hang; Cheng, Guo; Haggarty, Rachel; Batra, Akshay; Afzal, Nadeem A; et al.
Abstract : Background: Thiopurine drugs have been widely used in the treatment of IBD for several decades. In recent years, a better understanding of thiopurine metabolism has resulted in optimising treatment doses based on the metabolite profiles rather than the conventional weight-based dosing. For the major metabolite 6-TGN, levels between 235–450 pmol are adopted in IBD treatment guidelines as therapeutic thresholds associated with increased likelihood of efficacy and reduced risk of cytopenias, whereas 6-MMPN > 5700 pmol is associated with hepatotoxicity. There is a scarcity of studies in the paediatric population assessing the association of thiopurine metabolite profiles with the treatment doses used. Aims: This study investigates the relationship between weight-based thiopurine dosing and thiopurine metabolite levels in a paediatric IBD cohort. Methods: The study included children recruited to the 'Genetics of Paediatric IBD Study- Southampton', diagnosed with IBD before the age of 18 years. Thiopurine metabolite levels were retrospectively recorded in paediatric patients on a stable dose of thiopurines for at least 2 months alongside drug doses adjusted for weight at the time of metabolite testing, TMPT activity and other key descriptive features. Patients were excluded from the final analysis if concurrent dose and weight measurements were not available at the time of thiopurine metabolite testing. Patients with documented non-compliance were also excluded. Results: The study assessed data from a total of 376 paediatric patients with IBD; males- 218 (58%) and females- 158 (42%), median duration of follow-up- 51 months (IQR, 29- 81). A total of 251 readings measuring 6-TGN levels with concurrent dosage (mg/kg) were available in 99 patients (azathioprine= 153 measurements in 69 patients, 6-mercaptopurine= 98 readings in 30 patients). The median dose of azathioprine was 1.99 mg/kg (IQR 1.62- 2.25) and 6-mercaptopurine 1.19 (IQR 0.86- 1.4). The median dose of azathioprine and 6-mercaptopurine to achieve 6-TGN levels in the therapeutic range (235–450) was 2.01 mg/kg (IQR 1.64- 2.27, n= 60 measurements) and 1.26 (IQR 0.92- 1.39, n=41) respectively. The median dose observed to exceed the therapeutic upper limit of 450 pmol was very close at 2.11 (IQR 1.7- 2.34, n= 47 measurements) and 1.15 (IQR 0.8–1.45, n= 32 measurements) for azathioprine and 6-mercaptopurine respectively in individuals with normal TPMT activity. In the azathioprine group: 6-TGN levels correlated positively with the drug dose/kg (p=0.0047); 6-TGN levels correlated negatively with TMPT activity (p= 0.0083), but the association did not reach statistical significance when patients with TPMT activity below the normal reference range were excluded (p= 0.07). In the 6-mercaptopurine group: no significant association was observed for 6-TGN levels with dose/kg (p= 0.452) as well as with TPMT activity (p= 0.439 including all patients, p=0.476 for patients with normal TPMT). No significant gender differences were observed for 6-TGN and 6-MMPN. Conclusions: Our study shows that toxic levels of metabolites can be seen even when thiopurines are prescribed within the 'safe' prescribing dose range and despite normal TPMT levels. Thiopurine metabolites should be routinely monitored in all patients treated with thiopurines for better and safer outcomes.